Muscle strength testing: use of normalisation for body size. - Jaric, S. (Sports Medicine, 2002)
Assessment of muscle strength tests has been a popular form of testing muscle function in sports and exercises, as well as in other movement-related sciences for several decades. Although the relationship between muscle strength and body size has attracted considerable attention from researchers, this relationship has been often either neglected or incorrectly taken into account when presenting the results from muscle strength tests. Two specific problems have been identified. First, most of the studies have presented strength data either non-normalised for body size, or normalised using inappropriate methods, or even several different normalisations have been applied on the same sets of data. Second, the role of body size in various movement performances has been neglected when functional movement performance was assessed by muscle strength. As a consequence, muscle function, athletic profiles, or functional movement performance assessed by tested muscle strength have been often confounded by the effect of body size. Differences in the normalisation methods applied also do not allow for comparison of the data obtained in different studies. Using the following allometric formula for obtaining index of muscle strength, S, independent of body size (assessed by body mass, m) should be recommended in routine strength testing procedures: The allometric parameter should be either b = 0.67 for muscle force (recorded by a dynamometer), or b = 1 for muscle torque (recorded by an isokinetic apparatus). We also recommend using body-size-independent indices of both muscle strength and movement performance when assessing functional performance from recorded muscle strength or vice versa.